Kemampuan Berpikir Kreatif Siswa SMA Ditinjau dari Strategi Pemecahan Masalah - Atika Dwi Wahyu Utari; Anggy Alya Novita; Averylla Dwi Endri Prastiya; Nonik Indrawatiningsih (Universitas Negeri Surabaya, 2026)
Creative thinking ability is one of the essential competencies in the 21st century, particularly in solving mathematical problems. This study aims to analyze high school students’ creative thinking skills in terms of their problem-solving strategies. This research employed a qualitative descriptive approach involving three students from class XI selected purposively based on their level of problem-solving strategy use: high, moderate, and low. Data were collected through problem-solving tests and interviews, then analyzed using Miles and Huberman’s model: data reduction, data display, and conclusion drawing. The results showed that students with high creative thinking ability used three varied strategies, demonstrated logical reasoning, and displayed originality when facing unfamiliar problems. Students with moderate abilities met two indicators, namely flexibility and originality. Meanwhile, students with low abilities did not meet any of the creative thinking indicators. These findings indicate that the more diverse and systematic the problem-solving strategies used by students, the higher their level of creative thinking. This research suggests that developing students’ creativity in mathematics should be encouraged by presenting open-ended problems and implementing learning models that emphasize multiple strategies and independent thinking.